The genetics of neurodevelopmental disease - MITCHELL, KEVIN (Elsevier, 2011)
The term neurodevelopmental disorder encompasses a wide range of diseases, including recognizably distinct syndromes known to be caused by very rare mutations in specific genes or chromosomal loci, and also much more common disorders such as schizophrenia, autism spectrum disorders, and idiopathic epilepsy and mental retardation. After decades of frustration, the past couple of years have suddenly seen tremendous progress in unravelling the genetics of these common disorders. These findings have led to a paradigm shift in our conception of the genetic architecture of common neurodevelopmental disease, highlighting the importance of individual, rare mutations and overlapping genetic aetiology of various disorders. They have also converged on specific neurodevelopmental pathways, providing insights into pathogenic mechanisms.
PUBLISHED
Keywords: Genetics; Neuroscience; neurodevelopmental disorder